2023
DOI: 10.1111/clr.14064
|View full text |Cite
|
Sign up to set email alerts
|

Implant stability changes over time following implant placement in elderly patients: A prospective study

Abstract: Objectives This study aimed to evaluate the effect of aging on the changes in implant stability over time following implant placement. Materials and methods A total of 104 patients in four age ranges (group 1: <60 years, group 2: 61–70 years, group 3: 71–80 years, and group 4: >80 years) were included. Bone‐level tapered implants were placed without implementing any bone augmentation procedure. The final torque value displayed on the implant engine during implant insertion was recorded. Cone‐beam computed tomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…For similar reasons, implant treatment of old patients is increasing worldwide (Choi et al, 2023). According to several authors (Del Amo et al, 2022;Raikar et al, 2017), the overall success rate, after a period of observation, in the older patients was equal or even slightly better than in the younger group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For similar reasons, implant treatment of old patients is increasing worldwide (Choi et al, 2023). According to several authors (Del Amo et al, 2022;Raikar et al, 2017), the overall success rate, after a period of observation, in the older patients was equal or even slightly better than in the younger group.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies, on the other hand, have shown that the old population has increased life expectancy not only in terms of duration but above all in the increase in the healthy part of life (Aliberti, De Caro, et al, 2022 ; Aliberti, Funk, et al, 2022 ; Aliberti et al, 2023 ). For similar reasons, implant treatment for old patients is on the rise worldwide (Choi et al, 2023 ). In agreement with Köndell et al ( 1988 ), who compared the success rate of 284 implants in 53 old patients, aged 65–85 years with the success rate of 183 implants in 36 younger patients, aged 18–54 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prerequisite for clinical success of dental implants is osseointegration, defined as a direct structural and functional connection between the bone and the surface of the implant [ 6 , 7 ]. Elderly patients undergoing implant surgery are at higher risk compared to younger patients owing to their age-related health conditions [ 8 ]. With an increase in age, bone quality and quantity deteriorate, leading to osteoporosis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%